Novel Approach for Efficient Recovery for Spinal Cord Injury Repair via Biofabricated Nano-Cerium Oxide Loaded PCL With Resveratrol to Improve in Vitro Biocompatibility and Autorecovery Abilities. Issue 3 (1st September 2020) - Dong, Liang; Kang, Xin; Ma, Qiang; Xu, Zhengwei; Sun, Honghui; Hao, Dingjun; Chen, Xiujin
It is more difficult to develop the low-cost spinal cord injury repair materials with high stability and biocompatibility for the biomedical applications. Herein, for the first time, we demonstrated the functional restoration of an injured spinal cord by the nano CeO2 particles assembled onto poly (∊-caprolactone) (PCL)/resveratrol (RVL) were synthesized using the biocompatible ionic liquid. The as-prepared biocompatible nanomaterials were characterized and confirmed by using different instruments such as Fourier transform infra-red spectroscopy for functional groups identification, X-ray diffraction for crystalline nature, Scanning electron microscopy, transmission electron microscopy for morphological structure, Dynamic light scattering for size distribution of the nanoparticles and thermogravimetric analysis for thermal properties. The synergetic effect between the uniform distributions of nano-sized CeO2 particles onto the PCL polymer with RVL can remarkably enhance the catalytic performance. Biofabricated nano-cerium oxide loaded PCL with RVL revealed that treatment significantly preserved hydrogen peroxide and also good catalytic performance. This study presents a nano-sized cerium oxide particles loaded PCL with RVL biocompatible materials have been providing highly efficient regenerative activity and biocompatibility in spinal card regeneration.